Strategi dan Analisis Pemasaran Usaha Home Industri Cuanki Asep Pride Sebagai Upaya Meningkatkan Volume Penjualan - Muhammad Sugiharto; Deayu Handayani (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Cuanki is a Bandung specialty dish originally derived from the Tim Sam (dim sum) trademark with a sauce known as Bakso Tahu Kuah Choan Kie—where “Choan Kie” in Hokkien means “luck.” One business actor engaged in this sector is Cuanki Asep Pride, located in Jagabaya Village, Cimaung District, Bandung Regency. This business is a home industry that experienced fluctuating sales from 2009 to 2024, with the most significant decline occurring in 2020 due to the impact of the COVID-19 pandemic. This sales instability demonstrates the importance of an appropriate marketing strategy to create value and build long-term relationships with customers. This study aims to identify internal and external factors that influence Cuanki Asep Pride's business, as well as formulate a marketing strategy based on a SWOT analysis. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the SWOT analysis indicate that the business is in quadrant I of the SWOT matrix, which means the company has significant strengths and opportunities that can be maximized. The recommended strategy is a growth-oriented strategy, which includes: improving product quality, more targeted promotions, providing promotional tools such as social media, strengthening competitiveness through product uniqueness, digitizing business processes, utilizing digital platforms for sales, and controlling prices to increase consumer purchasing power. This strategy is expected to help expand market reach and increase sales volume sustainably.